2019
DOI: 10.1142/s1013251119500024
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Media and Emotion in South Korea’s Presidential Impeachment Protests

Abstract: Previous studies have shown that social media is effective in large-scale mobilization, facilitating leaderless and more flexible forms of resistance. However, some scholars argue that this type of mobilization suffers from a lack of organizational form and collective identity. This paper shows that social media-centered networks can in fact promote collective actions powerful enough to challenge a corrupt president. We also prove the role of emotions in collective actions. Using an empirical analysis of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…However, according to a survey on a representative sample of Korean electorate with a size of 1, 200 undertaken in December 2016, 23.9 percent of respondents replied that they participated in the demonstrations (Lee et al, 2017). Other research based on different surveysthus, different samplesreport similar results, for example Kim (2017) and Min and Yun (2019). An interesting finding in Lee et al (2017) is that they did not find big differences between the participants and ;non-participants in terms of demographic as well as socio-economic characteristics other than the fact that the respondents of 60s and older were not likely to participate in the demonstrations.…”
Section: The Beginning Of Candlelight Demonstrationsmentioning
confidence: 59%
See 2 more Smart Citations
“…However, according to a survey on a representative sample of Korean electorate with a size of 1, 200 undertaken in December 2016, 23.9 percent of respondents replied that they participated in the demonstrations (Lee et al, 2017). Other research based on different surveysthus, different samplesreport similar results, for example Kim (2017) and Min and Yun (2019). An interesting finding in Lee et al (2017) is that they did not find big differences between the participants and ;non-participants in terms of demographic as well as socio-economic characteristics other than the fact that the respondents of 60s and older were not likely to participate in the demonstrations.…”
Section: The Beginning Of Candlelight Demonstrationsmentioning
confidence: 59%
“…The voluntary citizens filled the rest. That is, the Action remained faithful to the role of the periphery, accepting the nature of diverse backgrounds and weak ties among the participants (Bennett and Segerberg, 2012;Min and Yun, 2019). It appears that what united the citizens with diverse backgrounds was the angermore precisely, the feeling of indignationwith Park Geun-hye and the way her administration worked, accumulated over the previous years and finally found a way out in the presence of hard evidence.…”
Section: The Beginning Of Candlelight Demonstrationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, Min and Yun (2019) focused on anger and determined, in the field of political communication and in South Korea, that this emotion plays a fundamental role in social networks when it comes to promoting or intensifying the force of social mobilizations. These authors concluded that the emergence of negative emotions, especially anger, is a more determining factor when the number of participants in a social protest increases, much more than the specific object of that protest or other factors, such as the personal agenda or the greater or lesser availability of the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Business communication is presented as the main subject of research by Chmiel et al (2011) , de Vries et al (2012) , Teixeira et al (2012) , Cvijikj and Michahelles (2013) , Goh et al (2013) , Hollebeek and Chen (2014) , Hudson et al (2015) , Hudson et al (2016) , Kim et al (2015) , Khan et al (2016) , Marbach et al (2016) , Dessart (2017) , Kim and Yang (2017) , Schultz (2017) , Swani and Milne (2017) , Swani et al (2017) , Xu and Wu (2017) , Rout et al (2018) , Vignal Lambret and Barki (2018) , and Moussa (2019) . Personal communication is analyzed in studies by Mauri et al (2011) , Meshi et al (2013) , Nelson-Field et al (2013) , Brynielsson et al (2014) , Coviello et al (2014) , Tandoc et al (2014) , Carrillo et al (2015) , Ferrara and Yang (2015) , Lin and Utz (2015) , Lee and Hong (2016) , Wang et al (2017) , Fan et al (2018) , Ng and Kozlowski (2018) , Turel et al (2018) , Vermeulen et al (2018) , Barry et al (2019) , Min and Yun (2019) , Nash et al (2019) , Ranganathan and Tzacheva (2019) , and Sion (2019) .…”
Section: Discussionmentioning
confidence: 99%